CAREER INTEREST IN ISLAMIC BANKING: THE ROLE OF REPUTATION, RELIGIOSITY, AND FINANCIAL REWARDS - Nada Cantika Putri Kadua; Muhammad Usamah Al-Azamy (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2025)
This study aims to examine the effects of corporate reputation, religiosity, and financial rewards on the career interest of Islamic banking students in pursuing employment within Islamic banks. The sample consists of 137 students majoring in Islamic Banking from three universities: UIN Sunan Kalijaga, Universitas Ahmad Dahlan, and Universitas Alma Ata. Data were collected using a Likert-scale questionnaire and analyzed through Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach using SmartPLS 4.0. The novelty of this study lies in its integrated examination of organizational, financial, and spiritual dimensions as predictors of career interest in the Islamic banking sector, a combination that has been rarely explored simultaneously in previous research. Additionally, by focusing on students from multiple universities with distinct institutional backgrounds, this study provides a more comprehensive and comparative understanding of factors shaping career aspirations in Islamic finance. This research is important to conduct because Islamic banks in Indonesia continue to face challenges in attracting highly motivated and competent young professionals, despite the sector’s rapid growth. Identifying the determinants that shape students’ intention to pursue careers in Islamic Banking is crucial for improving talent acquisition strategies, designing more appealing employer value propositions, and strengthening the long-term sustainability of the Islamic financial industry. The findings indicate that corporate reputation, religiosity, and financial rewards have a positive and significant influence on students’ interest in pursuing a career in Islamic Banking.